2018
DOI: 10.1200/po.17.00098
|View full text |Cite
|
Sign up to set email alerts
|

Reflex Testing for GermlineBRCA1,BRCA2,PALB2, andATMMutations in Pancreatic Cancer: Mutation Prevalence and Clinical Outcomes From Two Canadian Research Registries

Abstract: Purpose We investigated the translational value of reflex testing for germline mutations in four homology-directed DNA repair predisposition genes ( BRCA1, BRCA2, PALB2, and ATM) in consecutive patients with pancreatic adenocarcinoma. Methods One hundred fifty patients with French-Canadian (FC) ancestry were evaluated for founder mutations, and 114 patients were subsequently assessed by full gene sequencing and multiplex ligation-dependent probe amplification for nonfounder mutations. Two hundred thirty-six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…Although our study was not sufficiently powered to detect the prevalence of individual rare genes, the frequency of mutations in genes such as BRCA1/2 was in the range of what has been previously reported for primarily non-Ashkenazi cohorts. 8,12,24 For example, we found that 2.7% of the patients (8 of 298) had mutations in BRCA1/2, whereas 1.8% of the patients (15 of 854) in the Hopkins cohort did, with both studies finding less than a 1% prevalence of mutations in PALB2 (1 of 298 and 2 of 854). Likewise, Lowery et al found that only 1 of 615 patients with pancreatic cancer had a germline mutation in PALB2.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Although our study was not sufficiently powered to detect the prevalence of individual rare genes, the frequency of mutations in genes such as BRCA1/2 was in the range of what has been previously reported for primarily non-Ashkenazi cohorts. 8,12,24 For example, we found that 2.7% of the patients (8 of 298) had mutations in BRCA1/2, whereas 1.8% of the patients (15 of 854) in the Hopkins cohort did, with both studies finding less than a 1% prevalence of mutations in PALB2 (1 of 298 and 2 of 854). Likewise, Lowery et al found that only 1 of 615 patients with pancreatic cancer had a germline mutation in PALB2.…”
Section: Discussionmentioning
confidence: 74%
“…12,28 In addition, trials evaluating poly(adenosine diphosphate ribose) polymerase inhibitors in PDAC patients with germline mutations in BRCA1/2 or PALB2 are ongoing (National Cancer Institute 8993 and NCT03140670). Other than mutations in BRCA1/2, mutations in ATM and CHEK2 were most common in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations